Low water contents in garnet of orogenic peridotite: clues for an abyssal or mantle-wedge origin? - Schmädicke, Esther; Gose, Jürgen (European Journal of Mineralogy, 2019)
Data on water in nominally anhydrous minerals (NAMs) of orogenic garnet-bearing ultramafic rocks (GBU) are extremely rare. In this study, garnet of peridotite and pyroxenite from Erzgebirge (EG), Germany, and two peridotite samples from Alpe Arami (AA), Switzerland, were analyzed by infrared (IR) spectroscopy. Garnet from EG peridotite and pyroxenite yielded IR absorption bands at 3650 +/- 10 cm(-1) (type I) and in the wavenumber range of 3570-3630 cm(-1 )(type II) that are ascribed to structural hydroxyl (colloquially "water"). Additional broad band's centered at <3460 cm(-1), present in about half of the samples, are related to molecular water (MW). The content of structural H2O defined by band types I + II is low (3-68 ppm) in all EG samples. Structural water is negatively correlated to Mg and Ti and positively to Y and HREE in EG garnet. Including molecular water, a pronounced positive correlation between H2O and Li is observed. Because the intensity of the type II band is enhanced in domains with molecular water, the primary, peak metamorphic H2O content in EG garnet was probably as low as 0-11 ppm. Equally low contents of structural water are present in AA garnet (10-13 ppm) in which molecular water is negligible. Such concentrations are distinctly lower than the water storage capacity of garnet at the relevant pressure. Water loss upon decompression cannot serve as an explanation for the low contents because, on the contrary, post-peak-metamorphic influx of H2O led garnet to take up secondary structural water. Hence, the results are interpreted as an indication of severe water deficiency at peak metamorphism. Notably, the obtained data agree with the H2O content of 6 ppm reported in garnet from Cima di Gagnone peridotite, which originated as abyssal peridotite. It remains unknown if these low contents are typical for an abyssal, low-pressure protolith but, if the rocks were part of the lowermost, most hydrated portion of the mantle wedge, they are expected to contain much more water. Given that garnet in basaltic coesite eclogite from the Erzgebirge is equally water-deficient as the GBU samples from the same unit, it is at least a possibility that both rock types share a low-pressure origin in an oceanic setting.
CRIS-Team WoS Importer:2019-11-29